2020
DOI: 10.1051/parasite/2020061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Trypanosoma brucei gambiense in naturally infected pigs, dogs and small ruminants confirms domestic animals as potential reservoirs for sleeping sickness in Chad

Abstract: Human African trypanosomiasis (HAT) has been targeted for zero transmission to humans by 2030. Animal reservoirs of gambiense-HAT could jeopardize these elimination goals. This study was undertaken to identify potential host reservoirs for Trypanosoma brucei gambiense by detecting its natural infections in domestic animals of Chadian HAT foci. Blood samples were collected from 267 goats, 181 sheep, 154 dogs, and 67 pigs. Rapid diagnostic test (RDT) and capillary tube centrifugation (CTC) were performed to sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
8
18
0
Order By: Relevance
“…The global results obtained with BCT, TL and PCR confirmed high trypanosome infection rates in pigs as already observed in previous studies conducted on the neighboring Bonon and Sinfra HAT endemic foci [11,39] or in other study areas in West and Central Africa as in Nigeria [40], Chad [41] or Cameroon [42][43][44]. Such high infection rates in pigs may be linked to their tolerance to trypanosomes as already observed in the field [20] or during experimental infections with T. b. gambiense [45], and certainly illustrate that the pig is a preferential host for tsetse flies [46,47].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 87%
See 2 more Smart Citations
“…The global results obtained with BCT, TL and PCR confirmed high trypanosome infection rates in pigs as already observed in previous studies conducted on the neighboring Bonon and Sinfra HAT endemic foci [11,39] or in other study areas in West and Central Africa as in Nigeria [40], Chad [41] or Cameroon [42][43][44]. Such high infection rates in pigs may be linked to their tolerance to trypanosomes as already observed in the field [20] or during experimental infections with T. b. gambiense [45], and certainly illustrate that the pig is a preferential host for tsetse flies [46,47].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 87%
“…These results confirm that the CATT is not specific of T. b. gambiense due to cross-reactions with other trypanosomes as already observed [51][52][53][54]. The SD Bioline HAT rapid diagnostic tests (RDT) [55], another serological test initially developed for HAT diagnosis, also showed a lack of T. b. gambiense specificity when used in animals [41,56,57]. In absence of serological tests adapted for field diagnosis of African trypanosomiases in animal surveys, we propose the use of CATT as screening methods, despite their lack of T. b. gambiense-specificity.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 86%
See 1 more Smart Citation
“…gambiense in two human samples from the Maro area. It was detected in one child and one older man confirming the presence of the parasite in the area and the ongoing risk of HAT infections, as it was also identified in animal reservoirs reported by Vourchakbé et al ., 2020 [ 44 ]. These two participants have had no previous infection with this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…There are a considerable number of reports of Trypanosoma brucei gambiense parasites in both wildlife and domestic livestock -Büscher et al [7] provide a concise recent summary and, in addition, a recent study reported T. b. gambiense infections in domestic animals in Chad with 1.2-4.5% of those sampled testing positive in the three main foci [8]. Furthermore, experimental evidence of transmission of T. b. gambiense from animals back to humans, through the tsetse vector, has been documented [9], demonstrating that it is possible for animal-tsetse-human transmission cycles to exist.…”
Section: Introductionmentioning
confidence: 99%